Peningkatan Academic Engagement Siswa melalui Penerapan Model Problem Based Learning di Madrasah Tsanawiyah - Alimul Muniroh; I Nyoman Sudana Degeng; Imanuel Hitipeuw; Nur Hidayah (Universitas Negeri Malang, 2016)
Abstract: This study was conducted to determine the improvement of students' academic engagement through the implementation of problem based-learning model in the madrasah. This study used single subject design with multiple baseline across subjects. The subjects served as intervention targets as well as the control participant. There are four students as participants. They were chosen based on both the result of subject identification through instruments of Academic Engagement Scale for Grade School Students (AES-GS) and the result of observation to students with the lowest grades. The results of the graph analysis showed the decreased behavior in baseline phase but increased in the intervention phase. Key Words: academic engagement, problem based learning, Madrasah Tsanawiyah   Abstrak: Penelitian ini dilaksanakan untuk mengetahui peningkatan academic engagement siswa melalui penerapan model Problem Based Learning (PBL) di madrasah. Penelitian ini menggunakan rancangan eksperimen subjek tunggal dengan desain multiple baseline across subject. Subjek penelitian yang diintervensi sekaligus sebagai control participant. Jumlah subjek penelitian sebanyak empat siswa. Subjek penelitian dipilih berdasarkan hasil identifikasi subjek melalui instrumen academic engagement scale for grade school students (AES-GS) dengan perolehan hasil nilai paling rendah dan hasil observasi terhadap siswa yang menunjukkan nilai stabil rendah. Hasil analisis grafik pada kondisi baseline menunjukkan perilaku academic engagement stabil rendah, namun pada kondisi intervensi perilaku academic engagement meningkat.   Kata kunci: academic engagement,  problem based learning, Madrasah Tsanawiyah